Equilibrium Factor Pricing with Heterogeneous Beliefs - Handa, Puneet; Linn, Scott C. (Journal of Financial and Quantitative Analysis, 1991)
This paper develops an equilibrium factor pricing theory when investors have heterogeneous beliefs about asset payoffs generated by the Ross linear factor model. Investors receive private information about the unknown parameters of the payoff process. They use this private information and equilibrium prices to predict asset payoffs. The paper develops a closed form price function for a noisy rational expectations equilibrium and relates it to the general solution. Even though we allow for a large number of investors, diversity of beliefs and parameter uncertainty both persist in equilibrium. We show that investors' beliefs about expected payoffs are approximately linear in the asset's betas, thus establishing the APT. As investors prefer to hold high information assets in equilibrium, the relative weight of these assets in the APT pricing bound is higher. The reverse is true for low information assets.